Surface properties of nitrided layer on aisi 316l austenitic stainless steel produced by varied time low-temperature thermochemical treatments - Mahmoud, H.R.S. (Asian Research Publishing Network, 2016)
Recently, there are several attempts to improve the surface properties of AISI 316L by the mean of thermochemical treatments. The expected result is a layer on the surface termed expanded austenite which is supersaturated with nitrogen and carbon and this structure is responsible for the higher hardness and better wear properties without impairing its corrosion resistance. In this work, AISI 316L stainless steel was gas-nitrided/carburized simultaneously at 450 Â°C in quartz tube furnace for 8, 24 hours of treatment time. The morphological changes, structural phase, and elemental profile were observed by an optical microscope (OM), scanning electron microscopy (SEM) and energy dispersive X-ray (EDX). All the characterization methods confirmed the formation of nitrides and carbides on the surface layer of AISI 316L forming the expanded austenite layer (S phase), which leads to enhancement of surface properties of the nitrided samples. Â©2006-2016 Asian Research Publishing Network (ARPN).